Stress management training program for stress reduction and coping improvement in public health nurses: a randomized controlled trial - Alkhawaldeh, Ja'far M.; Soh, Kim Lam; Mukhtar, Firdaus; Ooi, Cheow Peng; Alkhawaldeh, Hamzeh M.; Al-Amer, Rasmieh; Anshasi, Huda A. (Wiley-Blackwell Publishing, 2020)
Aims: This study aimed to evaluate the effect of the stress management interventional program in reducing occupational stress and improving coping strategies among public health nurses.